POVERTY AND CRIME AS ATTRACTION: HOW DID THE FILM “CITY OF GOD” SHAPE THE TOURIST IMAGE OF BRAZILIAN FAVELAS? - Damas, Helton Luiz Gonçalves (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
The study aims to analyze the regime of representation established by the film "City of God" and its role in constructing a tourist imaginary about brazilian favelas. The film "City of God" achieved significant international recognition and drew global attention to the social dynamics inherent to these areas. The research highlighted that the depiction of favelas, while evoking repulsion, also transforms these "territories" into fascinating and attractive places for a particular figure: the tourist. The methodology employed to fulfill the research objectives involved the development of a study based on qualitative analysis, gathering data through the examination of the film "City of God" and journalistic materials. The data generated from the journalistic texts were coded and processed using the IRAMUTEQ software. As concluding remarks, the study found that films serve as cultural products that shape favelas as objects of both repulsion and fascination. Consequently, they play a significant role in constituting the favela as a tourist attraction.